Exploring how people with dementia can be best supported to manage long-term conditions: a qualitative study of stakeholder perspectives. Issue 10 (8th October 2020) - Rees, Jessica Laura; Burton, Alexandra; Walters, Kate R; Leverton, Monica; Rapaport, Penny; Herat Gunaratne, Ruminda; Beresford-Dent, Julie; Cooper, Claudia
Abstract : Objectives: To explore how the self-management of comorbid long-term conditions is experienced and negotiated by people with dementia and their carers. Design: Secondary thematic analysis of 82 semi-structured interviews. Setting: Community settings across the United Kingdom. Participants: 11 people with dementia, 22 family carers, 19 health professionals and 30 homecare staff. Results: We identified three overarching themes: (1) The process of substituting self-management : stakeholders balanced the wishes of people with dementia to retain autonomy with the risks of lower adherence to medical treatments. The task of helping a person with dementia to take medication was perceived as intermediate between a personal care and a medical activity; rules about which professionals could perform this activity sometimes caused conflict. (2) Communication in the care network: family carers often communicated with services and made decisions about how to implement medical advice. In situations where family carers or homecare workers were not substituting self-management, it could be challenging for general practitioners to identify changes in self-management and decide when to intervene. (3) Impact of physical health on and from dementia : healthcare professionals acknowledged the inter-relatedness of physical health and cognition to adapt care accordingly. Some treatments prescribed for long-term conditions were perceived as unhelpful when not adapted to the context of dementia. Healthcare professionals and homecare workers sometimes felt that family carers were unable to accept that available treatments may not be helpful to people with dementia and that this sometimes led to the continuation of treatments of questionable benefit. Conclusion: The process of substituting self-management evolves with advancement of dementia symptoms and relies on communication in the care network, while considering the impact on and from dementia to achieve holistic physical health management. Care decisions must consider people with dementia as a whole, and be based on realistic outcomes and best interests.